Anomie and post-imperial transition: anti-Jewish violence in Galicia and the Czech Lands, 1918-1919 - Kutílek, Jan (My University, 2024)
This article explores anti-Jewish violence in Galicia and the Czech Lands during 1918–1919,  revealing  dynamics  amidst  the  collapse  of  the  Austrian  monarchy.  The  interconnected  factors of economic hardships, and nationalism were manifested differently in each region. The delegitimization  of  state  power  served  as  a  backdrop,  with  attacks  on Jews  expressing  dissat-isfaction with the old order. Both territories witnessed Jews targeted during hunger riots, em-phasizing the blend of economic discontent and anti-Jewish sentiments. Robust national consciousness played a pivotal role, although accompanied by a strong social revolutionary factor. Symbolic acts of violence expressed a moral economy that condemned the perceived hoarding and  immoral  profiteering  and  Jewish  impure  relationship  with  God.  While  both  regions  faced  violent  outbreaks,  Galicia  endured  incomparably  more  severe  and  deadly  violence.  This  comparative analysis provides insights into the complex dynamics that shaped post-monarchy East Central  Europe,  crucial  for  understanding  the  complexities  surrounding  anti-Jewish  violence  during  this  revolutionary  period.  Furthermore,  this  comparative  analysis highlights  how  different socio-cultural and economic contexts influenced violence against Jews, simultaneously shedding light on the larger process of nation-building in post-World War I East Central Europe.
Anomie a postimperiální transformace: protižidovské násilí v Haliči a českých zemích v letech 1918-1919
Keywords: anti-Jewish violence; Czechoslovakia; Poland; 1918; protižidovské násilí; Československo; Polsko; 1918